Pteridófitas da Serra do Caraça, Minas Gerais, BrasilBelo Horizonte Minas GeraisFevereiro de - Raquel Stauffer Viveros (2010)
The Serra do Caraça is located in the east border of Quadrilátero Ferrífero, in southern Serra do Espinhaço, comprising part of Catas Altas, Santa Bárbara and Mariana municipalities. The main preservation area is RPPN Santuário do Caraça with 10.187,89 ha. The altitude varies between 750 and 2072 m. The vegetation is composed of a mosaic of field and forest formations. This work is about the survey of pteridophyte species in this range, manly inside the RPPN limits. Consultations to the BHCB and OUPR herbaria were done and also six field expeditions. Two hundred and thirty six taxa were identified, representing 27 families, 74 genera, 234 species, two subspecies and seven varieties. The most representative families were: Polypodiaceae (37 spp.), Dryopteridaceae (34 spp.), Pteridaceae (29 spp.), Hymenophyllaceae (19 spp.), Thelypteridaceae (15 spp.), Blechnaceae, Cyatheaceae (13 spp. each) and Aspleniaceae (12 spp.), summing up 75,64% of the total. The most representative genera were: Elaphoglossum (26 spp.), Thelypteris (14 spp.), Blechnum (12 spp.), Asplenium, Cyathea (10 spp. each), Anemia, Hymenophyllum (nine spp. each), Lindsaea, Lycopodiella (seven spp. each), Selaginella, and Sticherus (six spp. each), representing 49,57% of the total. Most species occur on forest formations. Seventy six (32,20%) species are restricted to Brazil, 53 (69,74%) of which are restricted to the Southeast and South region, and also Bahia state. Sixteen species (6,84%) are in risk of extinction in Minas Gerais state. Some of the most important records of those are: Huperzia rubra (Cham. & Schltdl.) Trevis., Culcita coniifolia (Hook.) Maxon, Eriosorus flexuosus (Kunth) Copel. var. flexuosus, Eriosorus sellowianus (Kuhn) Copel., Micropolypodium perpusillum (Maxon) A.R. Sm, Lycopodiella benjaminiana P. G. Windisch, and Cochlidium pumilum C. Chr. The species number is greater than recorded for any area of Atlantic Forest in the Serra do Mar (costal range) and Serra da Mantiqueira, regions considered as the richest in pteridophytes in Brazil. The RPPN Santuário do Caraça is the second more important conservation unit for the protection of pteridophytes threatened by extinction in Minas Gerais state, only overcame by the Parque Nacional do Caparaó. Identification keys to the genera and species are provided, also with genera diagnoses and comments about morphology, informations on environments occurrence, geographic distribution, examined materials and illustrations of some diagnostic characters.